Harga Diri dan Kepuasan Pernikahan Terhadap Kualitas Hidup Ibu Rumah Tangga yang Tidak Bekerja - Fairuz, Farah; Satriadi, Sendi (Universitas Muhammadiyah Purwokerto, 2022)
The decision between prioritizing home responsibilities or career aspirations has become a significant issue for women globally, impacting their quality of life. This quantitative study employs a cross-sectional design to explore the effects of self-esteem and marital satisfaction on the quality of life among non-working housewives. A purposive sampling method was used to select participants, and data were analyzed using multiple regression techniques. The findings reveal a significant relationship between self-esteem and quality of life, as well as between marital satisfaction and quality of life. Both self-esteem and marital satisfaction are found to significantly influence the quality of life of housewives. Future research should explore the impact of additional factors such as social support networks and personal aspirations on quality of life. Additionally, interventions aimed at strengthening self-esteem and marital relationships could provide valuable insights into improving overall well-being for this demographic.